Two secure non-symmetric role Key-Agreement protocols - Ghoreishi, S. (Asian Research Publishing Network, 2016)
Recently, some two-party Authenticated Key Agreement protocols over elliptic curve based algebraic groups, in the context of Identity-Based cryptography have been proposed. The main contribution of this category of protocols is to reduce the complexity of performing algebraic operations through eliminating the need to using Bilinear Pairings. In this paper, we proposed two novel Identity-Based Authenticated Key Agreement protocols over non-symmetric role participants without using Bilinear Pairings. The results show that our proposed schemes beside of supporting security requirements of Key Agreement protocols, require a subset of operations with low complexity in compare with related protocols in this scientific area.